Brand Communication During the Covid-19 Pandemic: Nature, Motivations, and Outcomes - Baah, J.A. (University of Ghana, 2024)
Communication has been established as being essential to the essence and endurance of brands. Consequently, brand communicators have found ways to engage their public even during crises. However, the existing scholarship does not adequately account for the strategic revisions that exigencies are engendering in brand communications. Extant work focuses on brand communications in situations where brands are the centre or sources of crises, with attention on reputation defence. With global exigencies expected to rise, particularly, pandemics in which both brands and their customers face existential and urgent threats, brands require more proactive communication approaches. This thesis therefore investigated the nature of brand communication during the COVID-19 pandemic by documenting key features that characterised brand messages. It also explored the reasoning and motivations of brand communicators that led to the message frames identified. Finally, the study examined audience responses to brand messages during the pandemic. A mixed-method approach was employed, incorporating interviews, content analysis, and a survey. The study was informed by the Attribution and the Situational Crisis Communication Theory (SCCT). Structural Equation Modelling was used to analyse the survey data while descriptive statistics and thematic analysis were employed for the content analysis and interviews respectively. The findings revealed that brands adopted a ‘care-for-you’ logic in their messaging, opting for a less combative approach in brand communication. The findings also indicate a desire to safeguard and exhibit concern for the well-being of consumers, while promoting business continuity and enhancing top-of mind awareness as brand motivations. Additionally, the study found the efficacy of this care logic in predicting purchase intention in the exigency of the pandemic. Informed by these findings, the study introduces 'brand care communication' as an approach to communication suited to exigencies. The research contributes to the understanding of effective brand communication strategies during crises and offers insights for future research.
PhD. Communication Studies
Keywords: Communication; scholarship; Situational Crisis Communication Theory (SCCT)